Abundancia y diversidad de los recursos ícticos aprovechados por la pesca recreativa en Barra del Colorado, Costa Rica - Chacón Chaverri, Didiher (Revista de Biología Tropical, 1996)
Fish abundance and diversity were studied between September 1991 and April 1993 in the northeast Caribbean coast of Costa Rica; including wetlands, rivers, estuarine and offshore ecosystems. The collections were made using reel and rod with artificial and live bait and sport fishing vessels. TOtal capture and CPUE (a relative abundance index) reached maximum values from October through February (840 fishes and 10 fishes/hour/month. respectively. Thirty species and 5632 individuals were collected. This system has onc highly conspicuous species. Centropomus parallelus, which is Ihe most abundan. Megalops atlanticus. Caranx sp.. Cichlasoma sp. and Pomadasys crocro represent 72% of the total biomass.